Adhesive selection for hybrid spot-welded/bonded single-lap joints: Experimentation and numerical analysis. (January 2016) - Marques, G.P.; Campilho, R.D.S.G.; da Silva, F.J.G.; Moreira, R.D.F.
Abstract: The applications of adhesive joints are increasing in various industrial applications because they offer several advantages over traditional methods. The combination of adhesive bonding with spot-welding enables some advantages over adhesive joints such as increased stiffness, and higher static and fatigue strength. This work relates to the adhesive selection for single-lap adhesive joints by the bonding and hybrid (bonded and welded) techniques with different overlap lengths ( L O ). The adhesives are the brittle Araldite AV138 ®, and the ductile Araldite ® 2015 and Sikaforce ® 7752. The experimental results were compared against a Finite Element (FE) study coupled with Cohesive Zone Modelling (CZM). The results validated the numerical technique and also showed varying strength improvements of the hybrid joints over bonded joints depending of the adhesive.